(untitled) - Stempleski, Susan (Oxford, 2007)
Talk Time is a three-level conversation course that provides speaking and listening practice based on everyday situations. Gentle progression of communicative activities in each lesson makes it ideal for less confident students. The Class CDs contain recordings of the vocabulary, listening sections, grammar sections, and conversations.
Keywords: English language,Listening; Foreign speakers